Optimal stock trading with personal taxes - Constantinides, George M. (Journal of Financial Economics, 1984)
The tax law confers upon the investor a timing option - to realize capital losses and defer capital gains. With the tax rate on long term gains and losses being about half the short term rate, the law provides a second timing option - to realize losses short term and gains long term, if at all. Our theory and simulation over the 1962–1977 period establish that taxable investors should realize long term gains in high variance stocks and repurchase stock in order to realize potential future losses short term. Tax trading does not explain the small-firm anomaly but predicts a seasonal pattern in trading volume which maps into a seasonal pattern in stock prices, the January anomaly, only if investors are irrational or ignorant of the price seasonality.